(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
This research aimed to survey the actions carried out by the State of Paraná to promote mental health to convicts of the prisional system, having taken place from 2009 up until 2019. To this end we’ve followed the Bibliographic and Documentary Qualitative Research methodology while searching, from which its results were then studied through the lens of the Contet Analysis by Laurence Bardin. We were able to categorize, analyse (Systematic Literature Analysis) and compare the laws from the State Government of Paraná and minutes from DEPEN PR until we properly worked out, by the end of the overall research, what what was actually going on regarding the guarantee of rights provided by law for the promotion of mental health policies to those deprived of their freedom, thereby concluding that despite the existence of such laws favourable to the furthering of this cause, its implementations proved to be wholly ineffective (hardly publicized) and/or very unintelligible.